If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(1n-3)-3n=63
We move all terms to the left:
-5(1n-3)-3n-(63)=0
We add all the numbers together, and all the variables
-5(n-3)-3n-63=0
We add all the numbers together, and all the variables
-3n-5(n-3)-63=0
We multiply parentheses
-3n-5n+15-63=0
We add all the numbers together, and all the variables
-8n-48=0
We move all terms containing n to the left, all other terms to the right
-8n=48
n=48/-8
n=-6
| 20+4(3x-5)=28 | | 2000=2.50v-5000 | | -12-4=-4n | | 63=-3n-5(n-3) | | 20=-9(2a-3) | | (1/8)^2−2n=16 | | -4n-4=-50 | | 3(j+1)-5=4 | | (5/12)=4x | | -16+3n=2 | | k-1=-14 | | -8-2j=2j+8 | | x/9+17=14 | | 9n-12=24 | | 5x−4=20−3x | | 3x^2+5x+5=4x^2-5x+20 | | F(1/2)=1/6x-3 | | 6n+2n-1=23 | | F(x)=1/6x-3 | | 4(8-6n)=32 | | 70=-8z+38 | | 11x+12x+1=23x+1-11 | | x=0.8873-0.1136/0.0599 | | -|9x3|=-5x-8 | | 2x4+-1/8=0 | | −12x−7=53 | | 5(-2x+5)-3x=-92 | | 10+2(3x-4)=2(4-x)-4 | | 7-0.5x=0.25x-1.5 | | 8x-3=-14x-52 | | 4a+12=7a–9.a= | | 3x^2-6x-2.75=0 |